Genetic Variations of Cytokines and Cytokine Receptors in Psoriasis Patients from China - Xiao-Lan Li; Chun-Feng Wu; Gui-Sheng Wu (International Journal of Genomics)
Psoriasis is a chronic inflammatory and hyperproliferative skin disease affected by both genetic and environmental factors. The aim of the present study was to investigate polymorphisms in a candidate gene family of interleukin (IL) in unrelated Chinese patients with psoriasis and control subjects without psoriasis. In this case-control study, 200 unrelated Chinese psoriasis patients and 298 age- and sex-matched control subjects were enrolled. Genomic DNA was prepared from peripheral blood obtained from all psoriasis patients and control subjects. We genotyped seven single-nucleotide polymorphisms (SNPs) in candidate genes of six ILs: IL4, IL10, IL12B, IL13, IL15, and IL23R, which have been shown in the literature to be associated with psoriasis in other ethnic groups. Among the seven SNPs in the six IL genes studied, only the rs3212227 in the IL12B gene was found to be associated with psoriasis at genotypic level in the studied population. The C/C genotype in the IL12B gene is a protective factor of psoriasis (P = 0.0218; OR = 0.51; 95% CI: 0.27–0.96) in Chinese. Furthermore, the studied Chinese population has extremely low minor allele frequency for IL23R. Together, the data reveal unique genetic patterns in Chinese that may be in part responsible for the lower risk for psoriasis in this population.